Strength of HRM systems and perceived organizational support as determinants of employment relationships: The perspective of HR managers and workers' representatives - Mirta Díaz-Fernández; Álvaro López Cabrales; Ramón Valle Cabrera (BRQ Business Research Quarterly, 2023)
This article seeks to explain and understand how the strength of a human resource management (HRM) system and perceived organizational support (POS) determine employment relationships (ERs) in organizations and the behaviors they generate in terms of organizational citizenship behavior (OCB) and intentions to remain (IR). A typology of ERs is proposed, considering perceptions about the HRM system (Ability, Motivation, and Opportunity [AMO] model), its strength, and POS. An analysis was adopted, looking into organizations in two separate studies in service sectors (hospitality and financial services), taking as informants to 130 and 87 HRM managers and 30 workers' representatives as proxies of organizations and employees, respectively. Cluster analysis and analysis of variance (ANOVA) were conducted, and results are congruent with theoretical frameworks such as Attribution Theory and Social Exchange Theory. Depending on how stakeholders understand the way in which the HRM system is implemented and the level of POS, certain ERs are developed and explain employees' responses in terms of OCB and IR behaviors.
Keywords: M1; 650; AMO HRM practices; Employment relationships; intention to remain; organizational citizenship behavior; perceived organizational support; strength of HRM system